(untitled) (Texas Journal of Engineering and Technology, 2022)
Using harmful gas emissions and low-grade non-required ore material, it is possible to obtain the starting material for establishing the production of manganese compounds and metallic manganese with a simultaneous invaluable environmental, economic, technological, energy, in general - a strategic effect